Counts of winter ticks on live-captured moose in western US - DeCesare, Nicholas (Zenodo, 2024)
Data include counts of winter ticks (ticks.hind) along transects of variable length (transect.cm.hind) on the rumps of live-captured moose in 5 western US states (state). Other attribute data include the moose ID, capture date, local moose density (density.category), migratory status (migratory), presence of other ungulates on shared winter range (shared.winter.range). A suite of climate metrics are also included for each record specific to that capture location and year, labelled according to the biological season during which they were summarized (q=questing [fall]; d=dropoff [spring]; s=summer) as described in the manuscript. Metrics include the proprortionate snow cover (SnowProp), amount of snow water equivalent during midpoint and endpoint of season (SWEmid, SWEend), mean temperature (TempMean), number of days below 0 and -20 degrees C (TempDays0, TempDaysm20), average relative humidity daily minimum and maximum (RHmin, RHmax), cumulative precipitation (Precip), and landcover category (landcover). Lastly, also included are quadratic terms for some variables (_2) and 10-year averages of each metric spanning the study period, 2013-2022, (_avg). Ticks were counted along transects through the hair of moose captured during winter. Analyses were focused specifically on ticks counted on the rump area. Transects varied in length so the length of transects was used as an offset term in models. Please see associated manuscript for methodological details regarding tick load data collection and associated attribute data.